THE CLINIC, THE MAIN METHODS OF THE DIAGNOSTICS AND TREATMENT OF EPIDURAL HEMATOMA - B.A. RAKHMONOV; R.N. BERDIEV (Avicenna Tajik State Medical University, 2020)
The review provides data on modern methods of diagnosis and treatment of epidural hematoma (EH). Data are given, such as the frequency of occurrence of this pathology, its structure, and the specifics of diagnosis and treatment with the determination of indications for the use of surgery interventions or use of conservative therapy. It should be emphasized that the frequency of EH occurrence remains high. Mortality, according to various authors, is from 7.5% to 29.4%. The fatality for EH of the posterior cranial fossa is particularly high, reaching 31.5%, and with concomitant intracranial damage it is 84%. Additional research methods, such as CT, MRI, echoencephalography, craniography and cerebral angiography, have a great importance in the diagnosis of this pathology. At the same time, there are different opinions of the authors about the informativeness of the above-mentioned survey methods. Analyzing the literature on the treatment of EH, the authors identified differences in tactics in the periods before the introduction and after the widespread use of CT in the practice of neurosurgical institutions. The results of surgical treatment of EH, still, do not satisfy clinicians.